Contractor All Risk insurance policy BGIC DZO ENG CAR P-0001 05 2018 AC BRAC University represented by Treasurer as Principal & MS BUCG-ABC JV - Brac University (Brac University, 2023)
This record consists of general correspondence regarding Contractor All Risk insurance policy BGIC DZO ENG CAR P-0001 05 2018 AC BRAC University represented by Treasurer as Principal & MS BUCG-ABC JV of BRAC University new campus project.